Exploring the Relationship Between Organizational Behavior and Job Satisfaction: Analysis Qualitative from PT. Mayora, TBK - Vadilla, Anatasya Eka; Fitria, Dinda; Wahjono, Sentot Imam (Golden Ratio of Data in Summary, 2025)
The purpose of this study is to evaluate the relationship between organizational behavior and job satisfaction at PT Mayora Indah Tbk. This study uses a qualitative descriptive approach and employs a literature review method, based on several previous journals and research reports. The results of the study indicate that the relationship between organizational behavior and job satisfaction shows that positive organizational behavior increases job satisfaction, which in turn can increase employee productivity and loyalty. These results help the management of PT. Mayora Indah Tbk develop better strategies to create a friendly work environment. It is hoped that this study will serve as a reference for further research on the relationship between organizational behavior and job satisfaction in various industries.